Circumstantial meanings in 'Tuesdays with Morrie : an old man, a young man, and life's greatest lesson,' a memoir a systemic functional perspective / Tong Su Hsien @ Alice Tong - Tong, Alice Su Hsien (2012)
The current study attempts to examine the use of Circumstantial elements in the memoir Tuesdays with Morrie: An old man, a young man, and life’s greatest lesson by Mitch Albom. Drawing from Halliday and Matthiessen’s (2004) System of Circumstantiation, this study aims to reveal the choices of Circumstantial elements in the data and relate how the choices are used to fulfill the text’s social purpose of recounting. The selected data is transcribed, coded, analysed and provided in distribution tables. The distribution of Circumstantial elements shows that Circumstance of Location (Place and Time) predominates the chosen texts with 50.34% confirming the common use of Place and Time to express a recount. Circumstance of Manner with 25.17% also holds an importance in recounting due to its nature in explaining how something took place. The work most relevant to the study of Circumstantiation is by Dreyfus and Jones (2011). Although there are a number of work on Transitivity namely by Manan (2001), Teo (2002), Sriniwass (2003), Chen (2005), Gallardo (2006), Tan (2007) and Siow (2008), less attention has been given solely on the analysis of Circumstantial elements. Hence, this study attempts to give importance to the System of Circumstantiation. Among the four types of Circumstances of Expansion, Enhancing plays a significant role in expanding a text as it predominates at 87.76%. This suggests that enhancing expressions of Extent, Location, Manner, Cause and Contingency play a significant role in recounting thus enriching the text. The other three types of Expansions are Extending, Elaborating and Projection which are not significant at only 2.72%, 1.36% and 8.16% respectively. This study proves to be invaluable to many who wish to explore deeper into Systemic Functional Linguistics and its application in narratives and memoirs. Besides, the current study may also help teachers and writers to better appreciate the importance of using Circumstantial elements to provide details concerning Place and Time.